A cross-sectional, quantitative study on the prevalence of psychological myths in students in KZN, South Africa - Hill, Claire (The IIE, 2020)
The literature on psychological myths has shown that there is a prevalence of myths in the general population and that a psychology course could have an impact on these myths. Most of the literature available on this topic is gleaned from an international context. A replication of the Gardner and Brown (2013) study was undertaken in a South African context. Using similar questions from the instrument of Gardner and Brown (2013), KZN psychology students were asked to answer the questionnaire off the Facebook platform. There were 20 participants. Descriptive content analysis was undertaken; and the findings revealed that at minimum an introductory psychology module did not have an impact on the prevalence of myths in KZN students. The researcher contributed to the psychology field by providing a South African study on psychological myths in students. It is advised that future research examines the factors such as age, educational level and gender to be possible influences on the prevalence of myths in students.
Keywords: Psychological myths; Prevalence; Tertiary students; South Africa